Selection of cotton lines for high oil content - Carvalho, Luiz Paulo de; Rodrigues, Josiane Isabela da Silva; Farias, Franscisco José Correia (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the oil content and characters related to fiber quality and yield in cotton lines (Gossypium hirsutum), in order to select genotypes with high oil content and acceptable levels of the other characters. Twenty-two F6 lines and three checks were cultivated in three field trials – two in the municipality of Apodi, in the state of Rio Grande do Norte, and one in the municipality of Barbalha, in the state of Ceará, both in Brazil. The genetic parameters and the genetic gain from selecting 20% of the lines were estimated according to their means in each environment and in the group of environments. Regarding oil content, there is genetic variability, and the selection based on the overall mean is indicated, since this character showed high heritability, with 4.58% expected gain. The lines selected with this criterion have oil contents between 23.52 and 24.51%, which are higher than those of the Brazilian cultivar BRS Aroeira with the highest grain oil content (22.04%).